2022
DOI: 10.1038/s41598-022-23849-8
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Parenting Stress Index-Short Form used in the Japan Environment and Children’s Study

Abstract: The Parenting Stress Index-Short Form (PSI-SF) has been widely employed to assess parenting stress in a number of research and clinical trials. To date, no parenting stress studies in Japan have examined the factor structure, validity, and reliability of the PSI-SF. Therefore, this study aimed to evaluate the psychometric properties of this 19-item version as administered in a national cohort study, the Japan Environment and Children’s Study, to two sample groups of mothers, those with a 1.5-year-old child and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This instrument was developed to evaluate postpartum parenting stress based on the 78-item PSI [ 18 ], which had itself originated from Abidin’s 101-item PSI [ 1 , 19 ]. The J-PSI-SF has good internal consistency (Cronbach α = 0.87), test–retest consistency over a 1-year interval ( r = 0.73), and a three-factor structure composed of difficult child, parental distress, and spouse factors [ 20 ] ( ).…”
Section: Methodsmentioning
confidence: 99%
“…This instrument was developed to evaluate postpartum parenting stress based on the 78-item PSI [ 18 ], which had itself originated from Abidin’s 101-item PSI [ 1 , 19 ]. The J-PSI-SF has good internal consistency (Cronbach α = 0.87), test–retest consistency over a 1-year interval ( r = 0.73), and a three-factor structure composed of difficult child, parental distress, and spouse factors [ 20 ] ( ).…”
Section: Methodsmentioning
confidence: 99%
“…14 The number of food eliminations was defined by the number of parental reported food allergy reactions with eliminations by the questionnaire. As for outcome variables, we used the validated Japanese version of the Parenting Stress Index-Short Form (PSI-SF) with 19-item [16][17][18] 16 The confounder factors were place of recruitment, maternal age, maternal allergy history, maternal food allergy history, maternal highest education level, marital status, house income, siblings, sex, daycare center, stress events, partner's support, child's eczema, child's asthma, child's hay fever, and child's other allergic history.…”
Section: Variablesmentioning
confidence: 99%
“…Parenting stress was evaluated using the Japanese Version of the Parenting Stress Index-Short Form (Hatakeyama et al, 2022;Narama et al, 1999), which is based on a shortened version of the original English version of the Parenting Stress Index (PSI) developed by Abidin (Abidin, 1995). The PSI, as well as its shorter versions, have been used in studies of mothers of very preterm infants as a means of assessing their stress levels (Gray et al, 2018;Thomas et al, 2004).…”
Section: Parenting Stressmentioning
confidence: 99%
“…The PSI, as well as its shorter versions, have been used in studies of mothers of very preterm infants as a means of assessing their stress levels (Gray et al, 2018;Thomas et al, 2004). The scale consists of 19 items: 9 items regarding the 10 children's characteristics and 10 items about themselves (Hatakeyama et al, 2022;Narama et al, 1999). As with the original version of the PSI, the version used in this study is also reported to have high internal consistency (α = 0.87) and test-retest reliability (r = 0.73) (Hatakeyama et al, 2022).…”
Section: Parenting Stressmentioning
confidence: 99%
See 1 more Smart Citation